2014
DOI: 10.1590/s0102-8650201400160005
|View full text |Cite
|
Sign up to set email alerts
|

Animal model of chronic kidney disease using a unilateral technique of renal ischemia and reperfusion in White New Zealand rabbits

Abstract: PURPOSE:To establish a model of chronic kidney disease in White New Zealand rabbits, using an exclusive unilateral technique of renal ischemia and reperfusion. METHODS:Twenty males White New Zealand rabbits were used. All animals were subjected to the following: pre-surgical blood collection (1 st collection) for creatinine and urea serum analysis, left renal ischemia and reperfusion surgery technique, another blood sample was collected after 6 weeks post surgery (2 nd collection), the last blood sample (3 rd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Bazzano et al 5 observed that 10-min unilateral renal IR in rats worsened urinary parameters (protein, urea, glucose, fractional excretion of potassium and urea, creatinine clearance, and activity of alkaline phosphatase and gamma-glutamyl transferase) 21 days after injury. Togoe et al 12 found that 20-min unilateral renal IR in rabbits led to histopathological lesions of the renal tissue and increased serum creatinine 80 days after injury. The creatine results in our study are consistent with those reported by Bazzano et al 5 and demonstrate that IR episodes, even for a few minutes, damage the kidneys and result in progressive RD.…”
Section: Discussionmentioning
confidence: 99%
“…Bazzano et al 5 observed that 10-min unilateral renal IR in rats worsened urinary parameters (protein, urea, glucose, fractional excretion of potassium and urea, creatinine clearance, and activity of alkaline phosphatase and gamma-glutamyl transferase) 21 days after injury. Togoe et al 12 found that 20-min unilateral renal IR in rabbits led to histopathological lesions of the renal tissue and increased serum creatinine 80 days after injury. The creatine results in our study are consistent with those reported by Bazzano et al 5 and demonstrate that IR episodes, even for a few minutes, damage the kidneys and result in progressive RD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that an appropriate experimental animal model was essential for the pharmacological and pathological investigations of human diseases. Adenine is one of the most frequently used drugs for establishing CRF because, at large doses, it induces abnormalities in uric acid metabolism, resulting in abnormal increase in Cr and BUN, and inflammatory reactions which resemble those that occur in humans [21]. Currently, increasing evidence have demonstrated that polysaccharides derived from natural herbal medicines or foods are reliable and safe agents for treating some stubborn diseases via regulation of immunity [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…• Renal ischemia and reperfusion, by aseptic surgery [11][12][13] ; • Kidney damage was monitored for 14 days, using urine dipstick tests, in which renal damage was verified by the parameters pH, density, urobilinogen, and urinary glucose, as well as the presence of proteinuria and leukocytes. Renal damage was monitored for 14 days, using a urine reagent strip, by semiquantitative determination of 10 parameters by chemical reaction, in which the kidney was selected by the parameters pH, density, urobilinogen, and urinary glucose, in addition to the presence of proteinuria and leukocytes; • After 14 days of surgery for induction of kidney disease, the animals comprising the diseased groups were injected intraperitoneally (i.p.)…”
Section: Diabetes-associated Kidney Diseasementioning
confidence: 99%